Assessing Genetic Diversity among Foxtail millet (Setaria italica (L.) P. Beauv.) Accessions Using RAPD and ISSR Markers - Shingane, Smita; Patil, J. V.; Gomashe, Sunil; Chand, Dinesh (International Journal of Bio-resource and Stress Management, 2018)
Foxtail millet [Setaria italica (L.) P. Beauv.], is an important grain crop in temperate, subtropical, tropical Asia and in parts of southern Europe. In India it is cultivated in Andhra Pradesh, Karnataka, Tamil Nadu, Rajasthan, Madhya Pradesh and some parts of Maharashtra. The present study was conducted to analyse the molecular diversity in the foxtail millet genotypes by using RAPD and ISSR markers and identify diverse accessions for use in varietal improvement programmes. A set of 44 foxtail millet accessions selected from Kolhapur (Western Maharashtra) region of India were analyzed using random amplified polymorphic DNA (RAPD) and inter simple sequence repeat (ISSR) markers. A total of 212 (135 RAPD and 77 ISSR) scoreable markers were generated with 29 RAPD and 19 ISSR primers. Average number of alleles generated by RAPD was 7.1 and ISSR was 6.41. Per cent polymorphism shown by RAPD primers varied from 62.50% to 100% and ISSR from 66.66% to 100%. The average PIC value for RAPD and ISSR was 0.74 and 0.73, respectively. The dendrogram generated using UPGMA revealed three major clusters, with 22 genotypes in one cluster and 20 genotypes in second cluster and two genotypes in third cluster. The genetic similarity matrices based on the Jaccard’s coefficient ranged from 0.374 to 0.964 and 0.35 to 0.98 for RAPD and ISSR, respectively. The genotypes KOFM 1, KOFM 14, KOFM 36, KOFM 89, KOFM 90, KOFM 94 and KOFM 95 were found superior for creating more variability in foxtail millet.